USING EMOTIONS: BIOLOGICAL AND SOCIAL FACTORS INFLUENCING EMOTION UNDERSTANDING AND ANTISOCIALITY - MACLELLAN, SUSANNE (2016)
People are guided by their emotions which in turn are a consequence of their understanding of others’ emotion expressions. Their skills to read and accurately identify others’ emotion expressions are a key ingredient for good emotion understanding. That is, accurate emotion identification can be considered as the first frontier of successful emotion understanding, and as the first step of a sequence which results in empathic responding. Impairment within this sequence might mean that the way people respond to their environment may not be appropriate or even cause harm to others. Children and adolescents with callous-unemotional traits have difficulties reading emotional cues correctly, specifically those cues which show others in distress. Such an impairment is thought to underlie a distinct pathway to severe and stable antisocial behaviour. Conventional methods of curbing the antisocial behaviour of children with high callous-unemotional traits such as punishment or time-out do not have the desired effect. Instead, this group of individuals seems to respond well to parental warmth and sensitive responding. Given that children start to learn early how to read and respond to emotions in an empathic manner through interactions, parents have a potential role by intervening early to foster good emotional and social skills even in children with high callous-unemotional traits. Study 1 tested whether adolescent boys with high callous-unemotional traits exhibit an impairment that is specific to distress cues such as fear, sadness or pain as difficulties to recognise such cues in others may impair typical inhibition to behave in an antisocial manner. In Study 2, it was expected that successful parental scaffolding is dependent on parent’s own emotion understanding skills, and therefore, study 2 investigated ways in which parents can scaffold emotion understanding in typically developing children, e.g. through talking about others’ emotion states and through engaging children in mutual eye gaze. Study 3 examined the impact that varying levels of child callous-unemotional traits have on parent-child interaction. Specifically, it was of interest whether children with high callous-unemotional traits are willing to engage with their parents on an emotional level permitting successful parental scaffolding. Parental understanding of emotions was tested in terms of promoting parental sensitive responsiveness. In sum, there are three main points the present thesis contributed: first, findings of Study 1 and 3 support a theory of emotion processing impairment that is not specific to fear or sadness, but describe a broader impairment of a failure to engage with the emotional environment and attend to salient emotional stimuli. Second, this thesis confirms the value of studying callous-unemotional traits in adolescents and young children as well as their parents. Third, findings of Studies 2 and 3 support the important role parents play in the lives of their children with callous-unemotional traits, specifically through their own emotion understanding